2017
DOI: 10.1111/psyp.12903
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity and regulation in individuals with psychopathic traits: Evidence for a disconnect between neurophysiology and self‐report

Abstract: Individuals with psychopathic traits often demonstrate blunted reactivity to negative emotional stimuli. However, it is not yet clear whether these individuals also have difficulty regulating their emotional responses to negative stimuli. To address this question, participants with varying levels of psychopathic traits (indexed by the Triarchic Measure of Psychopathy; Patrick, 2010) completed a task in which they passively viewed, increased, or decreased their emotions to negative picture stimuli while electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
3
20
1
Order By: Relevance
“…Our findings revealed a disconnect between physiology and self‐report in narcissistic children. A similar disconnect has been observed in other individuals with dark personality traits, such as psychopaths (Ellis, Schroder, Patrick, & Moser, ), and may reflect interoceptive blindness (such that individuals are unaware of their physiological responses) or denial (such that individuals deny their physiological responses, whether or not they are aware of them). The opposite pattern has been observed in socially anxious individuals.…”
Section: Discussionsupporting
confidence: 64%
“…Our findings revealed a disconnect between physiology and self‐report in narcissistic children. A similar disconnect has been observed in other individuals with dark personality traits, such as psychopaths (Ellis, Schroder, Patrick, & Moser, ), and may reflect interoceptive blindness (such that individuals are unaware of their physiological responses) or denial (such that individuals deny their physiological responses, whether or not they are aware of them). The opposite pattern has been observed in socially anxious individuals.…”
Section: Discussionsupporting
confidence: 64%
“…This finding is consistent with earlier studies that demonstrated similar relationships between boldness and a trait positive/negative affect, resiliency [92,89], and well-being [90]. Although boldness is also considered to be connected with diminished physiological and emotional responsiveness [91], our study did not confirm this in relation to positive affective states.…”
Section: Psychopathysupporting
confidence: 88%
“…However, we postulate that vulnerable narcissism will be positively related to momentary NA and negatively related to momentary PA (Hypothesis 3). Finally, taking into account the fact that meanness and disinhibition are related to primary and secondary psychopathy [75], and boldness is related to grandiose narcissism [73,89], and considering the results of recent research on triarchic psychopathy dimensions [90][91][92], we hypothesize that: boldness will be positively related to momentary PA and negatively related to momentary NA (Hypothesis 4); disinhibition will be negatively related to momentary PA and positively related to momentary NA (Hypothesis 5), and meanness will be negatively related to momentary NA (Hypothesis 6).…”
Section: Introductionmentioning
confidence: 99%
“…Psychopaths do evince a disconnect between their actions, their physiological and neurophysiological reactions, and their verbal reports (see, e.g. Ellis et al 2016). However, an alternative to their lying about being empathic is that they simply do not understand that they are unempathetic.…”
Section: Hard Truths About Empathy Measuresmentioning
confidence: 99%